TINGKATAN BAHASA BALI UNTUK PENGEMBANGAN PENDIDIKAN BERKARAKTER DI SD NEGERI 1 SINABUN - Paryatna, I. B. M. Ludy; Wirani, I.A. Sukma (Universitas Pendidikan Ganesha, 2015)
The implementation of activities refers to the use of micro design development education in schools by using the Total Physical Response Method and Direct Method. The findings obtained in this P2M is teachers are able to use methods appropriate to the character of Grade 4, 5, and 6, despite their varied abilities. Realising Saturday as the Balinese Language Day, speaking should be directed through storytelling and play so it is easy to control. Matching game for kids is a safe game and has a value of national character as Mecepetan (fast-velocity), Ngaba pabesen (communion words), and kulkuk ( race ). Shared value of the game is hard work, honesty, and appreciate the achievement. Other games also need to be explored in order to support learning processes Balinese language preferred by the students.Keywords : character , local knowledge , language level